Tako-tsubo syndrome in an adolescent. A case report - Ariel Efrén Uriarte Méndez; Nancy González Vale; Lisandra Muñoz López (Medisur)
Takotsubo syndrome is an acute stress cardiomyopathy, characterized by a regional abnormality of left ventricular wall motion, with a peculiar circumferential pattern that results in marked left ventricular bulging during systole. In Cuba, takotsubo syndrome has been published in adult patients, but it is considered a rare entity in children, so it was decided to make this report. The case of a 16-years-old adolescent, with a history of having given birth 44 days before at the time of admission, who was received at the Emergency Department in serious condition, with dyspnea, precordial pain, and manifestations of shock, for what she was immediately referred to the Pediatric Intensive Care Unit it is presented. The history of having had a stress trigger such as delivery by cesarean section, the electrocardiogram with signs of myocardial ischemia, and the typical echocardiogram, with dyskinesia of the apical segments of the left ventricle, allowed the diagnosis of takotsubo syndrome and direct treatment in that sense. This syndrome is rare in the pediatric age, therefore, it can present as a severe form and not be recognized, bringing prognostic implications.